MODELLING AND SIMULATIONS OF MANEUVERING CHARACTERISTICS AUGMENTATION SYSTEM ON NARROW-BODY TURBOFAN AIRCRAFT - Daffa Pratama, Muhammad
This research discusses the modelling and simulation of Maneuvering Characteristics Augmentation System (MCAS) for narrow-body aircraft and focusing on the influence of horizontal stabilizer adjustments on reducing angle of attack deviations. MCAS is an automatic control system specially designed to enhance aircraft’s maneuvering characteristics and provide stall protection. This research employs altitude hold with horizontal stabilizer incidence input and angle of attack-to-horizontal stabilizer incidence feedback simulations to analyze MCAS-like system performance during the climbing phase by linearizing aircraft’s equations of motion and deriving aerodynamic characteristics and trim condition. The altitude hold is made to serve as the base control system for both simulation types. Proportional gain and PI control methods are employed to accelerate settling time and reduce steady-state error, while regulator control and tracker control are applied to angle of attack feedback simulations. Results from horizontal stabilizer incidence input simulations indicate that while the horizontal stabilizer reduces angle of attack deviations, it fails to maintain altitude and does not decrease elevator deflection deviations. However, it narrows the range of hinge moment coefficient but increase the lower limit, resulting in increasing pilot workload. In feedback simulations, angle of attack deviations are successfully minimized, and altitude is maintained near the desired level. The feedback system with regulator control shows similar elevator deflection deviations to the altitude hold system with smaller horizontal stabilizer incidence required while the tracker control increases elevator deflection deviations and larger horizontal stabilizer incidence. Both of feedback systems features a wider range of hinge moment but reduced lower limit of coefficients, implying reduced pilot workload.